Die ASFINAC und das österreichische Modell der Fernstraßenfinanzierung. ASFINAG and the Austrian model of trunk road financing. - Beckers, Thorsten; Brenck, Andreas; Hirschhausen, Christian von; Klatt, Jan Peter (Deutscher Verkehrs-Verl., 2006)
Die Fernstraßen in Österreich umfassen ein Netz von ca. 2.000 km und bestehen aus den Autobahnen und den Schnellstraßen. Die Finanzierung des Fernstraßennetzes ist von der Republik Österreich an die Autobahnen- und Schnellstraßen-Finanzierungs-AG (ASFINAG) übertragen worden, die ein privatrechtliches Unternehmen im Besitz der Republik Österreich ist. Es werden die Grundstruktur der Fernstraßenfinanzierung (Abschnitt 1) und Detailaspekte der Bewertung und Bilanzierung (Abschnitt 2) betrachtet. Abschließend wird das österreichische Finanzierungsmodell für die Fernstraßen einer Gesamtbewertung unterzogen (Abschnitt 3). difu

Since 1997, the private law company Asfinag owned by the Republic of Austria, has been responsible for the provision of finance for the trunk road network. Against the backround of this modified method of financial arrangements, Asfinag has been granted a 50-year right to a so-called "enjoyment of fruits and benefits" (usufruct) that renders this company responsible fot the collection of user charges. Trunk road financing has, since that time, been arranged intirely by way of users' contributions, which thus secure the necessary funds. As a countermove to the usufruct grant, Asfinag is obliged to provide the financial support for the expansion, maintenance and operation of trunk roads with the helb of vignettes and user charges, and with finance secured from outside sources. Asfinag can thus realize expansion projects by varying its net indebtedness in line with the level of investment. Once the road construction and expansion phase is complete, the amortization of the debts incurred can be arranged to coincide woth teh end of the period of usufruct in the year 2047. difu
Keywords: Individualverkehr; Straße; Autobahn; Schnellstraße; Fernverkehr; Straßenbau; Finanzierung; Privatisierung; Verkehrsplanung; Straßenbelastung; Kostenvergleich; Bewertung; Reiseverkehr